Comportamiento inicial de Gmelina arbórea Roxb en terreno con distintas topografías en el sector Unión Manabita de la parroquia Malimpia, cantón Quinindé, provincia de Esmeraldas - Torres Realpe, Ruth Esther (2022)
The objective of the present investigation was to determine how the degree of inclination of the land influences the dasometric variables, such is the case of height and diameter, on the other hand, to evaluate the number of leaves present in each individual and the survival of the seedlings. at the time of establishing melina plantations. The plots with